Methods in Drug Abuse Research: Cellular and Circuit Level Analyses, 1st edition - Waterhouse, Barry D. (CRC Press, 2020)
The field of drug addiction and substance abuse, which was initially confined to behavioral studies, has broadened dramatically. It now includes a vast array of cellular and molecular approaches as well as sophisticated electrophysiological and neurochemical methodologies that bridge the gap between cellular/molecular events and behavior.